Ethnomedicinal plants in jalgaon district: current status - D.A. Patil2, Pawar Shubhangi1 and (Current Botany, 2011)
The remote villages and hamlets of Jalgaon district are repositories of indigenous knowledge about plant wealth. A total of 167 plant species with respect to their valid botanical names, family, local name, parts used, recipe, status whether wild or cultivated are presented disease-wise. Their floristic analysis in the region is presented. As many as 35 plant species are exotic which have been integrated with local traditions. Such a study would help to develop a database of medicinal plants and conservation for posterity. Jalgaon district is a treasure trove of medicinal plant species. If subjected to modern laboratory scrutiny, it would reveal new drugs or provide alternatives.